THE BELIEFS AND EFL PEDAGOGICAL PRACTICES OF MADRASAH TSANAWIYAH TEACHERS IN SAKRA BARAT EAST LOMBOK WEST NUSA TENGGARA - ., Sudarman; SEKEN, KETUT; Artini, L. P. (Universitas Pendidikan Ganesha, 2013)
Abstract This qualitative study focused on analyzing the teacher?s beliefs and pedagogical practices in EFL employed by the teachers at Madrasah Tsanawiyah at Sakra Barat. The subjects of this research were all of the English teachers of Madrasah Tsanawiyah in Sakra Barat. The data were collected through questionaire, interview, observation and document study. The data were analyzed by using Miles and Huberman (1984), interactive model. It was found that teachers of Madrasah Tsanawiyah at Sakra Barat, in teaching learning process had certain kinds of beliefs with regard to the teaching and learning process, namely, (1) Teaching grammar is important in EFL, (2) Drilling is effective (3) Language as medium of instruction, (4) Cooperative learning, (5) contextual materials in teaching, (6) communicative activities. Teachers? beliefs influence their pedagogical practices in teaching and learning process in the classroom reflected their beliefs. Keywords: Beliefs, EFL, and Pedagogical Practices.